Preliminary study of water quality index of stream at UiTM Pahang branch, Jengka campus / Farah Wahida Mohd Latib ... [et al.] - Mohd Latib, Farah Wahida; Othman, Zulhafizal; Muhamad, Noor Safwan; Bachok, Mohd Fairuz (Universiti Teknologi MARA Cawangan Pahang, 2019)
This study was carried out to determine the preliminary water quality status of stream at UiTM Pahang Branch, Jengka Campus based on the physicochemical and biological parameters. The sampling was conducted on rainy season with seven sampling points that were selected along the stream. A total of 10 water quality parameters were measured and analyzed using standard methods for the Examination of Water and Wastewater, APHA (2005). Malaysian Department of Environment Water Quality Index (DOE-WQI) was calculated and classified according to the National Water Quality Standard, Malaysia (NWQS). The physical and chemical variables were temperature, dissolved oxygen (DO), conductivity, pH, total dissolved solid (TDS), salinity, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), and ammonia-nitrogen (NH3- N). Based on Malaysian WQI, the water in this study area is classified as Class III, which is classified as ‘common of economic value and tolerant species and safe for livestock drinking’.